TEACHER’ ASSESSMENT OF YOUNG LANGUAGE LEARNERS IN SPEAKING SKILL - Nur Qonita Aulia; Nurul Intan Saputri; Albiansyah Albiansyah (LINGUA : JURNAL ILMIAH, 2021)
ABSTRACT Young learners are learners who have unique that can imitate something like a language easily. Therefore, to know a language, they need an environment surrounded by people who speak the language that is targeted and meaningful because of the context. In this globalization era, many people agree that the English language is such an important subject that used to communicate globally. Many people assumed that Speaking is an important skill to mastering the language, however, it is very hard for beginners to speak a foreign language, especially English. In Indonesia, the English language has been taught at every level of learners, even in kindergarten and primary level. People believe that learning English at an early age has many advantages because young learners still have flexible minds and malleable tongues which help them learn English words easily. Furthermore, young learners are of course different from adult ones. Further, this paper aims to analyze how the teacher designing a test of speaking skills for young learners and how the teacher assesses young language learners in speaking skills. This research used a qualitative descriptive method and to obtain the data, the researchers used to interview and video documentation to gather the data. There were 17 teachers Madrasah Ibtidaiyah in Tajurhalang as participants. This research found that most of the teachers in Tajurhalang are used storytelling (8) and some of them also use picture talks (2), oral presentation (2) description (2), and also question and answer (3) as a technique that used by the teachers in assessing young learner speaking skill further, most of teachers Madrasah Ibtidaiyah in Tajurhalang district are use fluency (6) and some of them use comprehension (5), vocabulary (5), and pronunciation (1) as a criterion in assessing students speaking skill. Above all, as a language teacher, we have to know the characteristics of young learners and designing a test to make sure young learners' language speaking skill and components because it will be an important role for teaching and learning process to young learners better. Keywords: Young Learners, Speaking Skill, Designing Test